German Cardiac Society Working Group on Cellular Electrophysiology state-of-the-art paper: impact of molecular mechanisms on clinical arrhythmia management - Thomas, Dierk; Christ, Torsten; Fabritz, Larissa; Goette, Andreas; Hammwöhner, Matthias; Heijman, Jordi; Kockskämper, Jens; Linz, Dominik; Odening, Katja Elisabeth; Schweizer, Patrick Alexander; Wakili, Reza; Voigt, Niels (Clinical research in cardiology, 2019)
Cardiac arrhythmias remain a common challenge and are associated with significant morbidity and mortality. Effective and safe rhythm control strategies are a primary, yet unmet need in everyday clinical practice. Despite significant pharmacological and technological advances, including catheter ablation and device-based therapies, the development of more effective alternatives is of significant interest to increase quality of life and to reduce symptom burden, hospitalizations and mortality. The mechanistic understanding of pathophysiological pathways underlying cardiac arrhythmias has advanced profoundly, opening up novel avenues for mechanism-based therapeutic approaches. Current management of arrhythmias, however, is primarily guided by clinical and demographic characteristics of patient groups as opposed to individual, patient-specific mechanisms and pheno-/genotyping. With this state-of-the-art paper, the Working Group on Cellular Electrophysiology of the German Cardiac Society aims to close the gap between advanced molecular understanding and clinical decision-making in cardiac electrophysiology. The significance of cellular electrophysiological findings for clinical arrhythmia management constitutes the main focus of this document. Clinically relevant knowledge of pathophysiological pathways of arrhythmias and cellular mechanisms of antiarrhythmic interventions are summarized. Furthermore, the specific molecular background for the initiation and perpetuation of atrial and ventricular arrhythmias and mechanism-based strategies for therapeutic interventions are highlighted. Current “hot topics” in atrial fibrillation are critically appraised. Finally, the establishment and support of cellular and translational electrophysiology programs in clinical rhythmology departments is called for to improve basic-science-guided patient management.